LKS Berbasis Model Eliciting Activities untuk Mengetahui Kemampuan Pemecahan Masalah Matematika di Kelas VIII - Risnina Wafiqoh; Darmawijoyo Darmawijoyo; Yusuf Hartono (Jurnal Elemen, 2016)
This study aims to determine the characteristics of Model Eliciting Activities a valid and practical, and determine the potential effect on the student worksheet for problem solving ability eighth grade students. The study resulted several characteristics of model eliciting activities which are including: (1) LKS developed customized with steps and learning the principles of Model eliciting Activities; (2) improve the ability of students LKS Model eliciting Activities related aspects, namely self-assessment, documentation and construk models share abilities and re-usability; (3) Each settlement problems in LKS, guidance is given on the wane; (4) Guidance is given less and less able to develop students' problem-solving abilities; (5) LKS Model eliciting Activities related to indicators of achievement of mathematical problem solving ability. Student Worksheet categorized as having potential effects on math problem solving ability of students who have a grade point average mathematical problem solving ability of 68.5, so the mathematical problem solving abilities 8.1 grade students includes both categories.